On-line monitoring of wastewater quality using a chemical sensor array - Bourgeois, Wilfrid (Cranfield University, 2002)
Real-time and on-line monitoring of wastewater quality is a subject of growing concern both in the United Kingdom and internationally. Global organic load parameters are traditionally used to define wastewater characteristics and to demonstrate that a wastewater treatment plant meets statutory law. However these measurements are mainly based on sample collection and retrospective analysis which can be time consuming. Existing on-line instruments remain limited by environmental factors, short lifetimes and fouling problems due to the harsh environment in which they have to be located. The recent availability of commercial sensor array instruments could offer a rapid and relatively simple technique for non-invasive monitoring. Cont/d.